Intelligent multi-dose medication controller for fever: From wearable devices to remote dispensers. (January 2018) - Medina, J.; Espinilla, M.; García-Fernández, Á.L.; Martínez, L.
Abstract: In this work, an Intelligent Medication Controller which analyzes the data streams from body temperature provided by a wearable device is proposed in order to dispense in a low-cost remote dispenser installed at home. The main innovation of our approach is a pharmacokinetic and pharmacodynamic analysis based on the successful fuzzy linguistic approach and fuzzy logic. This analysis provides accuracy and adherence to patient fever in the decision making of medication intakes, adequating the doses and waiting time based on previous intakes. In order to show its efficiency, a case study is presented, in which a complete range of fever episodes is analyzed to compare the decision making in medication intakes of antipyretics between the human expert and the proposed Intelligent Medication Controller. Our proposal has obtained an encouraging performance when recommending medication intakes in a flexible way and assuring a secure response for contraindication cases.